2021
DOI: 10.1002/ccd.30025
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous wave‐free ratio for guiding treatment of nonculprit lesions in patients with acute coronary syndrome: A retrospective study

Abstract: Background The aim of this study was to analyze the feasibility of a physiological coronary evaluation with the instantaneous wave‐free ratio (iFR) of nonculprit lesions in patients with acute coronary syndrome (ACS) successfully revascularized. Methods A multicenter registry including patients of four high‐volume PCI centers with ACS and underwent successful revascularization of the culprit vessel and had other nonculprit lesions that were physiologically evaluated with the iFR between January 2017 and Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Indeed, only around 15% of the patients had ACS at presentation in the main iFR trials; however, iFR results led to similar outcomes, regardless of clinical presentation [ 38 ], and similar results were also confirmed in large scale registries [ 39 ].…”
Section: Non-hyperemic Indexes: Instant-wave Free Ratio (Ifr)mentioning
confidence: 89%
“…Indeed, only around 15% of the patients had ACS at presentation in the main iFR trials; however, iFR results led to similar outcomes, regardless of clinical presentation [ 38 ], and similar results were also confirmed in large scale registries [ 39 ].…”
Section: Non-hyperemic Indexes: Instant-wave Free Ratio (Ifr)mentioning
confidence: 89%
“…Following the validation studies described above, NHPR share similar indications than FFR but additional specific clinical scenario’s have been investigated. For example, a retrospective study reported how to decide to perform a PCI with iFR in non-culprit lesions of patients presenting with ACS[ 74 ].…”
Section: Non-hyperemic Pressure Ratiosmentioning
confidence: 99%
“…Placing a stent on all coronary lesions seen on coronary angiogram without certifying the impact of these lesions can complicate the procedure and jeopardize the outcome of the patient. There are a lot of data showing that PCI guidance by invasive imagistic and physiological investigation methods improves the outcome of the patient, with clear cut-offs for assessments that can guide us to achieve the best result with an adequate percentage of MACEs at the mid-term follow-up [8].…”
Section: Conclusion and Implications For Clinical Practicementioning
confidence: 99%